Epidemiology, Pathogenesis, and Control of a Tick-Borne Disease- Kyasanur Forest Disease: Current Status and Future Directions - Shah, Syed Z.; Jabbar, Basit; Ahmed, Nadeem; Rehman, Anum; Nasir, Hira; Nadeem, Sarooj; Jabbar, Iqra; Rahman, Zia ur; Azam, Shafiq (Frontiers in Cellular and Infection Microbiology, 2018)
In South Asia, Haemaphysalis spinigera tick transmits Kyasanur Forest Disease Virus (KFDV), a flavivirus that causes severe hemorrhagic fever with neurological manifestations such as mental disturbances, severe headache, tremors, and vision deficits in infected human beings with a fatality rate of 3-10%. The disease was first reported in March 1957 from Kyasanur forest of Karnataka (India) from sick and dying monkeys. Since then, between 400-500 humans cases per year have been recorded; monkeys and small mammals are common hosts of this virus. KFDV can cause epizootics with high fatality in primates and is a level-4 virus according to the international biosafety rules. The density of tick vectors in a given year correlates with the incidence of human disease. The virus is a positive strand RNA virus and its genome was discovered to code for one polyprotein that is cleaved post-translationally into 3 structural proteins (Capsid protein, Envelope Glycoprotein M and Envelope Glycoprotein E) and 7 non-structural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5). KFDV has a high degree of sequence homology with most members of the TBEV serocomplex. Alkhurma virus is a KFDV variant sharing a sequence similarity of 97%. KFDV is classified as a NIAID Category C priority pathogen due to its extreme pathogenicity and lack of US FDA approved vaccines and therapeutics; also, the infectious dose is currently unknown for KFD. In India, formalin-inactivated KFDV vaccine produced in chick embryo fibroblast is being used. Nevertheless, further efforts are required to enhance its long-term efficacy. KFDV remains an understudied virus and there remains a lack of insight into its pathogenesis; moreover, specific treatment to the disease is not available to date. Environmental and climatic factors involved in disseminating Kyasanur Forest Disease are required to be fully explored. There should be a mapping of endemic areas and cross-border veterinary surveillance needs to be developed in high-risk regions. The involvement of both animal and health sector is pivotal for circumscribing the spread of this disease to new areas.